Pengukuran risiko dalam konsep manajemen risiko - Hakim, Ahmad Muqarrabin (Maliki Interdisciplinary Journal, 2023)
This observation is carried out to find out how to measure a risk that exists or will occur in the future for a company. Risk measurement is an attempt to determine the size of the risk that will occur. This is done to see the level of risk faced by the company, then see the impact of risk on company performance and prioritize which risks are most relevant. This risk measurement is carried out using 7 techniques, namely probability measurement, notional risk, risk sensitivity, risk viability, VAR approach, risk frequency and significance matrix, scenario analysis. It is hoped that this observation will help determine the relative importance of a risk and obtain the information needed by the Risk Manager in an effort to determine the most acceptable/best method and combination of methods in using risk management tools.